2019
DOI: 10.1016/j.watres.2019.114966
|View full text |Cite
|
Sign up to set email alerts
|

Passive sampling of organic contaminants across the water-sediment interface of an urban stream

Abstract: Passive sampling of organic contaminants across the water-sediment interface of an urban stream. Water Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…In addition, from the total set of targeted compounds selected as model EOCs, the artificial low-calorie sweetener acesulfame was the most widespread chemical and was detected almost constantly in all polluted streams in our study. This pattern is consistent with previous studies in which acesulfame has been reported as the most ubiquitous EOC in streambed sediments and groundwater across Europe [12,[30][31][32][49][50][51]. Thus, our findings strongly support the use of acesulfame as a marker of EOC pollution for application in management and regulation of surface and subsurface waters [49].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, from the total set of targeted compounds selected as model EOCs, the artificial low-calorie sweetener acesulfame was the most widespread chemical and was detected almost constantly in all polluted streams in our study. This pattern is consistent with previous studies in which acesulfame has been reported as the most ubiquitous EOC in streambed sediments and groundwater across Europe [12,[30][31][32][49][50][51]. Thus, our findings strongly support the use of acesulfame as a marker of EOC pollution for application in management and regulation of surface and subsurface waters [49].…”
Section: Discussionsupporting
confidence: 93%
“…EOCs were analyzed using a previously developed direct-injection ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method (Posselt et al 2018). A total of 37 polar organic substances (mostly pharmaceuticals and their transformation products) were selected based on their concentration ranges, detection frequency, degradation behavior, and potential persistence, as well as their occurrence on priority lists [12,[30][31][32]. Water samples were defrosted and vortexed and a sample volume of 800 µL was combined with 195 µL methanol and 5 µL of an internal standard mix.…”
Section: Sampling and Processing Of Eocsmentioning
confidence: 99%
“…Novel methods such as highly dynamic sampling of pore water [223], time-integrated passive sampling techniques [177], and isotopic techniques are under development and will allow better insights into hyporheic processes. Peter et al [33] injected visible dye into shallow HZ sediments in a known downwelling location and pinpointed the area where the labeled flowpath re-emerged to the stream.…”
Section: Methods Development and Methods Standardizationmentioning
confidence: 99%
“…For example, in a bench-scaled flume experiment designed to study hyporheic processes [175], TPs were detected, which were only formed in the sediment but released to the water, hinting at secondary contamination with TPs [176]. In particular, valsartan acid, a rather stable TP of the common blood pressure medication valsartan, forms in situ in the HZ [160,177] and significantly increases its concentrations in the surface water of wastewater receiving streams [178].…”
Section: Retention and (Bio)transformation Of Trace Organic Compoundsmentioning
confidence: 99%
“…In particular, the significance of a conductive streambed for water quality and aquatic habitats in urban stream management plans is more and more acknowledged 10 , 11 . Micropollutant removal in sediment–water interfaces has been investigated in a number of recent studies, in particular with regards to bank-filtration scenarios 12 14 and along vertical flowpaths in losing streams 15 , 16 . Transformation processes of many micropollutants in sediments have been found to be promoted in such transition regions due to their specific redox-sensitivity and their dependency on the diversity of the microbial activities and communities involved 15 , 17 .…”
Section: Introductionmentioning
confidence: 99%